Enhancement of seaweed polysaccharides (fucoidan and laminarin) on the phagocytosis of macrophages via activation of intelectin in blunt snout bream (Megalobrama amblycephala) - Li, Hongping; Liu, Yunlong; Teng, Yuting; Zheng, Yancui; Zhang, Minying; Wang, Xu; Cheng, Hanliang; Xu, Jianhe; Chen, Xiangning; Zhao, Xiaoheng; Ding, Zhujin (Frontiers in Marine Science, 2023)
Fucoidan and laminarin are polymolecular compounds that extracted from seaweed. As functional polysaccharides, they possess various biological functions such as immunomodulatory, anti-inflammatory, antiviral and antioxidant bioactivities. Fucoidan and laminarin modulate host immune responses by activating immune cells (macrophages, neutrophils, T lymphocytes) and inducing the expression of cytokines (TNFα, IL-1β, IL-6, IL-8, NF-κB). Intelectin is a novel lectin that plays important roles in bacterial agglutination and bactericidal effects by recognizing the polysaccharide components on the cell surface of pathogens, which can also enhance the phagocytosis of macrophages. The present study intends to explore the immunomodulatory effects of fucoidan, laminarin and intelectin on the macrophages of Megalobrama amblycephala. The results showed that the incubation of both fucoidan and laminarin at the concentration of 100 μg/mL for 4 h could enhance the phagocytic capacity of M. amblycephala macrophages, which also showed remodeled cytoskeleton with extended pseudopodia. In addition, fucoidan and laminarin could induce the expression of M. amblycephala intelectin (MaINTL) in the primary hepatocytes and macrophages, and the recombinant MaINTL (rMaINTL) could bind with fucoidan and laminarin. Furthermore, fucoidan and laminarin induced the expression of cytoskeletal remodeling related genes in the primary M. amblycephala macrophages, such as Rac1 and WASP, which should contribute to the enhancement of seaweed polysaccharides (fucoidan and laminarin) and MaINTL on the phagocytosis of M. amblycephala macrophages. However, even though fucoidan and laminarin could induced the expression of CXCL8, while the chemotaxis of M. amblycephala macrophages on neutrophils was not affected by them. These findings suggested that fucoidan and laminarin enhanced the phagocytic capacity of M. amblycephala macrophages via activation of MaINTL and up-regulation of the expression of downstream cytoskeletal remodeling related genes Rac1 and WASP. Therefore, fucoidan and laminarin could be used as immune enhancers to improve host immunity and disease resistance in M. amblycephala, which provided novel insights into the prevention and protection of fish bacterial diseases.